Management Of Oral Candidiasis Children And Infant With Hiv/Aids Infection : Report Of Two Cases - Rina Kartika Sari; Alrevo Panji Auradewa; Salma Qatrunnada Sayuti (Odonto : Dental Journal, 2023)
Background: HIV infection is characterized by progressive immunosuppression due to low absolute CD4 counts. The most common HIV-related oral disorder is oral candidiasis. Case(s): First case, A 10-month-old baby girl complained of white plaque on her hard palate since 3 months ago.She had experienced the same before and was treated with Nystatin then the lesion resolved. She was HIV positive and took Abacavir twice a day. The latest CD4 test was 3 months ago and the result was 1000 cells/ÂµL. The second case is an 8-year-old male patient who complained white lesion all over his mouth one week ago and treated by Nystatin for 7 days but the lesion has not resolved. He had confirmed HIV at 2.5 y.o and takes ARV regularly. The CD4 count three weeks ago was 8 cells/mm3. Both of them were diagnosed with acute pseudomembranous candidiasis Management: The first patient was given Nystatin oral suspension 4 times a day and the lesion resolved in 1 week. The caregiver instructed to clean the child's mouth with gauze regularly. The second patient was given fluconazole 150 mg tablets 3-6 mg/kg once a day for 14 days. Both of the lesions responded well to antifungal. Conclusion: Oral candidiasis in children with HIV often occurs in conditions of low CD4 and often appears as acute pseudomembranous candidiasis. Treatment of is adjusted to the PNPK HIV Kemenkes RI 2019 according to the level of disease